Quantitation Of Β-Sitosterol From Celastrus Paniculatus Willd. Using Validated High Performance Thin Layer Chromatography Method - DR. VIDYA DIGHE; SHREEDA ADHYAPAK; KANCHAN TIWARI (International Journal of Pharma and Bio Sciences, 2011)
A sensitive high-performance thin-layer chromatographic method has been established for quantitation of β-sitosterol from dried seed powder of Celastrus paniculatus Willd. Chromatographic separation was performed on TLC alumina plates precoated with silica gel 60F254 as the stationary phase with toluene-ethyl acetate-glacial acetic acid (6.0:1.5:0.1v/v/v) as the mobile phase. The plates were scanned densitometrically in the reflectance-absorbance mode at 580 nm. The method was validated for linearity, precision, limit of detection (LOD), limit of quantitation (LOQ), and accuracy. Linearity was found to be in the range of 40.00µg/mL to 100.00µg/mL with value of correlation coefficient (r) = 0.9986. Instrumental precision, repeatability and intermediate precision were determined to evaluate the precision of the method. The accuracy of the method was established by evaluating percent recovery of β-sitosterol at three different levels and it was found to be 98.52.